2017
DOI: 10.35536/lje.v22.isp.a1
|View full text |Cite
|
Sign up to set email alerts
|

Pakistan’s Experience with the Pakistan–China FTA: Lessons for CPEC

Abstract: As Pakistan enters the CPEC era, there is a sense of optimism as well as concern in the country, given the uncertain economic impact of this major collaboration between China and Pakistan. Using firm-level and trade data, we empirically test the impact of the 2006 free trade agreement (FTA) between the two countries on the productivity, size and value added of potentially affected Pakistani firms. These results have important policy implications for CPEC initiatives. We start with a difference-in-difference an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The study concluded that Pakistan's integration with China and ASEAN would be beneficial for enhancing the bilateral trade flows of all the members. In contrast, other studies argued that Pakistan–China FTA is more beneficial to China as compared to Pakistan (Musleh-ud-Din et al ., 2009; Chaudhry et al ., 2017; Qi and Irshad, 2015; Shaista, 2010; Ahmad, 2014). Musleh-ud-Din et al .…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The study concluded that Pakistan's integration with China and ASEAN would be beneficial for enhancing the bilateral trade flows of all the members. In contrast, other studies argued that Pakistan–China FTA is more beneficial to China as compared to Pakistan (Musleh-ud-Din et al ., 2009; Chaudhry et al ., 2017; Qi and Irshad, 2015; Shaista, 2010; Ahmad, 2014). Musleh-ud-Din et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2009) argue that the short-term effect of the FTA between Pakistan and China is tilted towards China. Chaudhry et al . (2017) found out that in the sector in which the tariffs are reduced by Pakistan for Chinese commodities, productivity and the value-added per worker have fallen relative to other sectors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies were conducted before and during the implementation period of PCFTA (Javaid & Jahangir, 2005;Musleh et al, 2009;Naved & Sarah, 2012;Shaista, 2010). Furthermore, the recently conducted studies about PCFTA (Ahmad, 2014;Chaudhry et al, 2017;Qi & Muhammad, 2015) do not provide a comprehensive empirical analysis for Pakistan and China simultaneously. Interestingly, none of these studies analysed the aspect of asymmetry between Pakistan and China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This modest effect of the Pakistan-China FTA rains some concerns too. Some of the significant concerns mention in the literature are about the goods convergence, utilization, productivity, and trade deficit (Ahmad 2017;Chaudhry et al 2017;Musleh-ud et al 2009;Pakistan Business Council 2012;Qi and Muhammad 2015). Musleh-ud et al (2009) discuss the issue of the utilization of Pakistan-China FTA.…”
Section: Literature Reviewmentioning
confidence: 99%